2023
DOI: 10.1590/1519-6984.250351
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of Panton-Valentine Leucocidin (pvl) gene among MRSA and MSSA isolates

Abstract: The present study was conducted in order to determine the frequency of pvl gene among the pathogenic and healthy population isolates of Methicillin Resistant Staphylococcus aureus (MRSA) and Methicillin Sensitive Staphylococcus aureus (MSSA). For this purpose, nasal swab samples were collected from the healthy individuals (to be used as controls, all the samples were collected irrespective of the sex and age factors), the pathogenic samples were collected from different patients suffering from skin &soft t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…In Tabassum et al study in 2023, among the pathogenic samples isolated from the wound, 100% MRSA was identified. They found that the pathogenic MRSA samples contained 46% of the pvl gene, which is more than the present study (19.35%) (46).…”
Section: Discussioncontrasting
confidence: 70%
“…In Tabassum et al study in 2023, among the pathogenic samples isolated from the wound, 100% MRSA was identified. They found that the pathogenic MRSA samples contained 46% of the pvl gene, which is more than the present study (19.35%) (46).…”
Section: Discussioncontrasting
confidence: 70%
“…The detection of tsst-1 and pvl genes is clinically significant because their expression can be associated with severe infections caused by this organism, such as severe pneumonia and toxic shock syndrome (21). In Tabassum et al's study, 49% of MRSA strains in the normal population and 46% in pathogenic MRSA strains carried the pvl gene, raising public health concerns (22). In another study, 19% of S. aureus strains were observed to be pvl-positive (23).…”
Section: Frequency Of Toxin Genesmentioning
confidence: 99%
“…Additionally, SAK also inhibits α-defensins, antimicrobial peptides that possess bactericidal properties ( Scudiero et al, 2020 ). Moreover, the Panton-Valentine leukocidin (PVL), a two-component toxin, leads to the formation of pores in leukocyte cell membranes ( Tromp and van Strijp, 2020 , Tabassum et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%